Exploration of Learning during an International Health Elective Using Photovoice Methodology - Amy Werremeyer; Elizabeth Skoy; Gina Aalgaard Kelly (MDPI AG, 2016)
Based on surveys and structured interviews, International Health Experiences (IHEs) improve cultural sensitivity, communication, and self-confidence among health professions students. However, open-ended methods to explore student learning during an IHE are not widely utilized. We sought to explore pharmacy student-identified learning during an IHE in an open-ended fashion using Photovoice methodology. Pharmacy students on an IHE in Guatemala were given disposable cameras and asked to photograph images that reflected their learning. Through the application of Photovoice methodology students captured, reflected upon, and presented photos to describe the learning they experienced. Themes were drawn from the reflective and focus group data collected. During three IHEs, six students captured seventy-seven photos. Four main learning themes emerged: culture/cultural competence, professional growth, shifting of attitudes, and meaningful/emotional experiences. Pharmacy students documented learning in expected (cultural competence, professional growth) and unexpected (emotional experiences) domains during an IHE. Photovoice may be an effective methodology for the exploration of learning, allowing students to capture their own learning including and beyond what is expected by their instructors.